2012
DOI: 10.1155/2012/528047
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Polyvinylpyrrolidone on the Optical Properties of the Ni‐Doped ZnS Nanocrystalline Thin Films Synthesized by Chemical Method

Abstract: We report the optical properties of polyvinyl-pyrrolidone (PVP) and the influence of PVP concentration on the photoluminescence spectra of the PVP (PL) coated ZnS : Ni nanocrystalline thin films synthesized by the wet chemical method and spin-coating. PL spectra of samples were clearly showed that the 520 nm luminescence peak position of samples remains unchanged, but their peak intensity changes with PVP concentration. The PVP polymer is emissive with peak maximum at 394 nm with the exciting wavelength of 325… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(14 citation statements)
references
References 35 publications
1
12
1
Order By: Relevance
“…22 Interestingly, luminescence peak of CdSe is found to be nearly at around 535 nm in the literature. 36 Whereas in our case, luminescence peak of CdSe is at 564 nm. This results in red shift of PL spectra of polymer nanocomposite for CdSe nanoparticles.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)contrasting
confidence: 45%
“…22 Interestingly, luminescence peak of CdSe is found to be nearly at around 535 nm in the literature. 36 Whereas in our case, luminescence peak of CdSe is at 564 nm. This results in red shift of PL spectra of polymer nanocomposite for CdSe nanoparticles.…”
Section: Fourier Transform Infrared Spectroscopy (Ftir)contrasting
confidence: 45%
“…[21] The conclusion about the existence of excitation energy-transfer processes between PVP molecules and ZnS nanoparticles is supported by the authors [22] that studied the PVP influence on optical and spectral properties of thin nanocrystalline ZnS films doped by Ni 2 + ions. Spectral and luminescent properties of PbS suspensions that were stabilized by high-molecular PVP (Ms = 1300000) were studied in Konstantatos et al [1] and Rowan.…”
Section: Introductionmentioning
confidence: 88%
“…To date, the non-conjugated polyvinylpyrrolidone (PVP) is mostly used as a passivator or a capping agent for semiconductor such as ZnS or CdS, with the purpose to reduce the agglomeration and improve the optical property [12]. Some studies reported the application of the PVP as a sensor [14,15]. Wang et al reported that the PVP can be used as electrochemical sensor for acyclovir molecule [14], while Zhang et al used PVP nanocomposite as a humidity sensor [16].…”
Section: Introductionmentioning
confidence: 99%
“…Wang et al reported that the PVP can be used as electrochemical sensor for acyclovir molecule [14], while Zhang et al used PVP nanocomposite as a humidity sensor [16]. Since the PVP has been also reported to have photoluminescence property [15], it is worthy to study the possibility to use the non-conjugated PVP as the fluorescence sensor. To the best of our knowledge, there is no investigation on the application of the PVP as the fluorescence sensor.…”
Section: Introductionmentioning
confidence: 99%